Concerning the Apparition of a Mobile Phone in a 17th Century Painting and Its Issuefication - Bakhtiar, Siavash (European Journal of Multidisciplinary Studies, 2018)
Through focusing on a specific case study of a viewer going to a museum and seeing for a short moment a mobile phone in a 17th century painting, this article aims to address the concerns of some modern thinkers who are extremely worried about the proliferation of information and communication technologies (ICTs) and their substitution of more traditional domestic artefacts. In response to the need to address the causes and consequence of this latent technophobia in critical theory, thinkers like Bruno Latour are looking for theoretical allies to build up a more accurate “Thing Theory.” This article argues that Latourian approaches, by offering sociologists and philosophers an enriched conceptual toolbox, open up more space in theory for non-human entities and recognise their affordance in the composition of what is usually called society.
Keywords: Thing Theory – quasi objects – material culture – Bruno Latour – object-centred theory – participatory objects – politics of artefacts – second empiricism A close up of Pieter de Hooch’s painting “Man Handing a Letter to a Woman in the Entrance Hall of a